2020
DOI: 10.21098/jimf.v6i1.1202
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Islamic Microfinance : Case Based Evidence From India

Abstract: This study examines Islamic microfinance as an important contributor to both the economic and human development of India. We are aware that conventional microfinance products have flourished in India; however, these products do not fulfil the needs of all Muslim clients. Taking small glimpses of Islamic microfinance (IMF),we can say it is working successfully in Muslim countries. From the meta-analysis we classify the literature into seven categories, viz. social benefits, religious values, business enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In Indonesia, besides being classified as banks, BPRS are also classified as Islamic microfinance institutions (MFIs) that aim to seek profits. BPRS also support the development of the social and economic aspects of society (Irfan, 2020). Accordingly, considering the important role of BPRS, understanding factors affecting BPRS performance is worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, besides being classified as banks, BPRS are also classified as Islamic microfinance institutions (MFIs) that aim to seek profits. BPRS also support the development of the social and economic aspects of society (Irfan, 2020). Accordingly, considering the important role of BPRS, understanding factors affecting BPRS performance is worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers benefitted from databases and software tools. The literature is likely to develop by including other respective databases such as WoS. Sector-based researches performed on Islamic finance such as takaful and sukuk, followed by Islamic funds, microfinance and other sectors (Aliyu et al , 2017; Irfan, 2020; Tahir, 2007). As in the first category, these studies are not capped into specific countries or research types.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sector-based researches performed on Islamic finance such as takaful and sukuk, followed by Islamic funds, microfinance and other sectors (Aliyu et al , 2017; Irfan, 2020; Tahir, 2007). As in the first category, these studies are not capped into specific countries or research types.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As result, they lack skills which make them be at disadvantage to secure a good job (Chaurasia, Priya & Agrawal, 2019;Richmond, Robinson, Sachs-Israel & Sector, 2008). Past studies have shown that the Islamic finance market is recording growth with an approach aiming at human increase people`s income through assisting small and medium enterprise and human well-being (AbdulKareem, Mahmud, Abdulganiyy & Yazid; Irfan, 2020). Interestingly, Islamic finance products especially Sukuk provides a useful instrument to fill the gap as social intermediation for illiteracy.…”
Section: Illiteracymentioning
confidence: 99%